Drought Adaptive Traits and Wide Adaptation in Elite Lines Derived from Resynthesized Hexaploid Wheat - Lopes, M.; Reynolds, Matthew P. (Wiley, 2011)
It has been shown previously that under drought, synthetic hexaploid derived wheat (Triticum aestivum L.) lines outperformed recurrent parents in part due to increased root mass at depth and better water extraction capacity. A group of four elite synthetic derived (SYN-DER) lines and parents was grown under full irrigation and drought conditions to dissect some of the physiological features conferring tolerance to drought. Synthetic derived wheat lines showed on average a 26% yield increase as compared to the parental hexaploid wheats under terminal drought. Different strategies for drought tolerance were observed, including earliness to flowering, greater root mass at depth, greater water extraction capacity, and increased water use efficiency (WUE) at anthesis. Some degree of independence was identified between these traits when comparing SYN-DER lines suggesting that these traits are regulated by different genes. The elite SYN-DER line Vorobey was an important source of improved root mass at depth under drought. We conclude that the use of wild species of wheat has the potential to improve a range of stress-adaptive traits and may permit modern bread wheat to become adapted to a wider range of environments including climate change scenarios.